Implementasi Etika Deep Ecology Dalam Perspektif Filsafat Hindu Di Desa Medahan Dan Desa Keramas - Somawati, Ayu Veronika (Jayapangus Press, 2025)
Water holds a highly significant position in the lives of Hindus, not only as a basic necessity but also as an essential element in religious and social activities. However, over time, the quality and quantity of water in Bali have degraded, including in the villages of Medahan and Keramas in Blahbatuh Subdistrict, Gianyar Regency. This research aims to rediscover the values of deep ecology ethics in the efforts to preserve the water sources in these two villages to ensure that the water sources remain sustainable and can be passed down to future generations. This research uses observation, interviews and documentation studies to collect data, as well as qualitative descriptive methods to present research results. Based on research results, it was found that Medahan and Keramas villages have numerous water sources that are socially and spiritually significant. The community preserves them through the construction of sacred sites, the instilling of beliefs about the importance of water sources, the installation of warning signs, and communal efforts to clean the water sources. These water conservation actions, practiced and passed down by the community, are closely linked to the principles of deep ecology ethics, which urge humans to respect nature and recognize the rights of nature as equal to human rights. This ethic asserts that all living beings possess intrinsic value and are deserving of moral consideration. The implementation of deep ecology ethics emphasizes love and reverence for nature, akin to love for God. This research shows that the preservation of water sources in Medahan and Keramas is not only an ecological action but also a spiritual expression that reflects harmony between humans, nature, and God.